A Hybrid Islamic Pedagogy Model for Generation Alpha Character Education in the Digital Era - Murdianto; Yorman; Azman Che Mat (TARBIYA: Journal of Education in Muslim Society, 2025)
Abstract Digital culture has influenced how students learn, interact, and form moral references, creating new challenges for character education in Islamic boarding schools. This study examines character education for Generation Alpha at Al-Raisiyah Islamic Boarding School, Sekarbela, Mataram, and formulates a digital-adaptive model grounded in pesantren traditions and Sasak local values. The research used a qualitative approach with an interpretivist paradigm and an intrinsic case study design. Data were collected from January to April 2025 through participatory observation, semi-structured interviews, and documentation studies. Participants included 14 Generation Alpha students, 6 kyai/ustadz, and 4 pesantren managers selected purposively. Data analysis followed the interactive model of Miles, Huberman, and Saldaña through data condensation, data display, conclusion drawing, and verification. The findings indicate that digital culture affects students’ concentration, learning patterns, and moral references. Al-Raisiyah responds through daily habituation, relational exemplarity of kyai and ustadz, communal supervision, Sasak cultural values, selective guidance in digital media use, and digital ethical literacy. The study proposes a hybrid Islamic pedagogy model that combines religious discipline, local wisdom, moral authority, and responsible digital engagement in pesantren education.   Abstrak Budaya digital telah memengaruhi cara siswa belajar, berinteraksi, dan membentuk rujukan moral, sehingga menghadirkan tantangan baru bagi pendidikan karakter di pesantren. Penelitian ini mengkaji pendidikan karakter Generasi Alpha di Pesantren Al-Raisiyah, Sekarbela, Mataram, dan merumuskan model adaptif berbasis tradisi pesantren serta nilai lokal Sasak. Penelitian menggunakan pendekatan kualitatif dengan paradigma interpretatif dan desain studi kasus intrinsik. Data dikumpulkan pada Januari–April 2025 melalui observasi partisipatif, wawancara semi-terstruktur, dan studi dokumentasi. Partisipan terdiri atas 14 siswa Generasi Alpha, 6 kyai/ustadz, dan 4 pengelola pesantren yang dipilih secara purposif. Analisis data mengikuti model interaktif Miles, Huberman, dan Saldaña melalui kondensasi data, penyajian data, penarikan kesimpulan, dan verifikasi. Hasil penelitian menunjukkan bahwa budaya digital memengaruhi konsentrasi, pola belajar, dan rujukan moral siswa. Al-Raisiyah meresponsnya melalui pembiasaan sehari-hari, keteladanan relasional kyai dan ustadz, pengawasan komunal, nilai budaya Sasak, bimbingan selektif penggunaan media digital, dan literasi etika digital. Penelitian ini menawarkan model pendidikan karakter berbasis pesantren yang menghubungkan disiplin keagamaan, kearifan lokal, otoritas moral, dan keterlibatan digital yang bertanggung jawab. Temuan ini memberi kontribusi praktis bagi penguatan pendidikan karakter pesantren di era digital secara berkelanjutan.